2005
DOI: 10.1038/sj.cgt.7700875
|View full text |Cite
|
Sign up to set email alerts
|

Iodide sensitizes genetically modified non-small cell lung cancer cells to ionizing radiation

Abstract: While external ionizing radiation has been used for treating non-small cell lung cancer (NSCLC), improved efficacy of this modality would be an important advance. Ectopic expression of the sodium iodide symporter (NIS) and thyroperoxidase (TPO) genes in NSCLC cells facilitated concentration of iodide in NSCLC cells, which markedly induced apoptosis in vitro and in vivo. Preincubation of the NIS/TPO-modified NSCLC cells in iodide followed by ionizing radiation generates bystander tumoricidal effects and potentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Studies have shown that Cx43 plays important roles in cancer development, cell proliferation, apoptosis, invasion and metastasis in lung cancer (20)(21)(22)(23)(24)(25)(26). Most importantly, Cx43 is able to sensitize NSCLC cells to CDDP and ionizing radiation (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Cx43 plays important roles in cancer development, cell proliferation, apoptosis, invasion and metastasis in lung cancer (20)(21)(22)(23)(24)(25)(26). Most importantly, Cx43 is able to sensitize NSCLC cells to CDDP and ionizing radiation (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that transfection of NSCLC cells with both human NIS and thyroperoxidase (TPO) genes resulted in an increase in radioiodide uptake rate and retention time [6] . Intraperitoneal injection of potassium iodide or iodide treatment followed by ionizing radiation markedly improved the efficacy in killing NIS/TPO-modified NSCLC cells [11,12] . However, many other charactertics of NIS are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of GJs to improve chemotherapy, Vance and Wiley suggested that ionizing radiation destroys not only targeted cells but also cells that have not been directly irradiated (the bystander effect) [ 125 ], and this effect is partially regulated by GJs [ 42 ], prompting GJIC as an appealing therapeutic target in combinatorial strategies with radiotherapy [ [126] , [127] , [128] ]. Zhang et al found that iodide-induced upregulation of Cx43 protein expression and Cx43-GJ activity in genetically-modified non-small cell lung cancer cells significantly increased the bystander tumoricidal effects generated by ionizing radiation, thereby enhancing tumor cell killing both in vitro and in vivo [ 43 ]. Furthermore, the authors suggested that iodide could also modulate a cascade of molecular pathways including RONS signaling through Cx43-GJs, to further sensitize non-small cell lung cancer cells to ionizing radiation and chemotherapies like paclitaxel [ 43 ].…”
Section: Therapeutic Strategies Applied To Cxs and Gjsmentioning
confidence: 99%
“…GJs have been shown to propagate oxidative stress-induced cell death [ 38 , 39 ], apoptotic cell death [ 40 , 41 ], and radiation-induced cell death [ 42 , 43 ] in cancer cells. This phenomenon is named the “bystander effect”, and refers to the transmission of responses from cells exposed to certain stimuli, to non-targeted neighboring or more distant cells by means of intercellular communication.…”
Section: Introductionmentioning
confidence: 99%